Desenvolvimento de um calorímetro utilizando uma placa de prototipagem eletrônica de hardware livre para o ensino de física - Barbosa, Rafael Rodrigues (2016)
It can be inferred that the Physics teaching in Brazil in high school has been being processed in an unconnected way to the science and technology production, in other words, favoring techniques of resolutions of exercises and formulae memorization. This traditional approach enhances the lack of interest by the student moving him or her away from the fields of basic science and engineering. The contribution of this study aimed to awake the scientific curiosity and the students? creativity, by means of the discovery and the meaningful learning. In order to do so, students from the second grade of high school developed a project in which it was used a free electronic hardware prototyping board. In this experiment, the students themselves developed a prototype of a calorimeter. So that the students could reproduce the study, tutorials were prepared based on the learning theory of David Ausubel and the theory of Vygotsky. The implementation of the experiment was by means of the project methodology and the learning assessment, by means of concept mappings. The calorimeter associated with a software of data acquisition made possible the study of the calorimetry. The results corroborated to the applicability of the methodology in the high school, showing itself to be of great potential in both the experimental dimension and in the contribution to the meaningful learning.